Inhibition of the DNA amplification of trypanosomes present in tsetse flies midguts: implications for the identification of trypanosome species in wild tsetse flies - Ravel S.; Mariani C.; Grébaut P.; Jamonneau V.; Cuisance D.; Cuny G. (Parasite, 2004)
The present study was carried out in order to investigate if there was really a failure of PCR in identifying parasitologically positive tsetse flies in the field. Tsetse flies (Glossina palpalis gambiensis and Glossina morsitans morsitans) were therefore experimentally infected with two different species of Trypanosoma (Trypanosoma brucei gambiense or Trypanosoma congolense). A total of 152 tsetse flies were dissected, and organs of each fly (midgut, proboscis or salivary glands) were examined. The positive organs were then analysed using PCR. Results showed that, regardless of the trypanosome species, PCR failed to amplify 40 % of the parasitologically positive midguts. This failure, which does not occur with diluted samples, is likely to be caused by an inhibition of the amplification reaction. This finding has important implications for the detection and the identification of trypanosome species in wild tsetse flies.